Using information technology to improve customer information and reduce workload for a filtration company - Botani, Qasim Mohammed Dalshad (2013)
This study presents the features of Micro-Mesh Company's web application. The study proposes a web application that has a number of features that will enhance customers' attitudes towards the company's website. These features include: the mobile interface; the live chat; the easily accessible Search Box; and the highly detailed FAQ page. These features will eliminate current IT problems and enhance the Micro-Mesh Company's competitive edge by improving customers' attitudes towards its website, increasing the number of repeat visitors, and escalating the volume of online purchases. The project's overall results show that the web application developed is functioning very well, meets Company's needs and is ready to be launched. The project can be evaluated as a successful achievement as the web application is being funded.